Towards efficient furfural production: A review of biphasic solvent systems for enhanced yields and industrial scalability - Namhaed, Kritsana; Kiatkittipong, Worapon; Cognet, Patrick; Najdanovic-Visak, Vesna; Kida, Tetsuya; Quitain, Armando T.; Assabumrungrat, Suttichai (Science, Engineering and Health Studies, 2025)
Furfural, a valuable platform chemical with wide industrial applications, has been produced for decades. Renewed interest in biorefinery processes has driven efforts to improve its production and expand industrial applications. However, challenges in achieving high furfural yield and purity after recovery remain significant bottlenecks. Coupling the reaction with simultaneous separation has emerged as a promising approach, with biphasic solvent systems gaining significant research attention. This review consolidates recent progress in using organic solvents within biphasic systems for furfural production from both simple sugars and raw biomass, covering both homogeneous and heterogeneous catalytic systems, as well as batch and continuous operation modes. Key topics include the formation and mechanisms underlying biphasic systems, which provide insights for process design, and an analysis of factors influencing furfural yields, aiding in reaction optimization. Strategies to enhance process efficiency-such as solvent selection and tuning, phase ratio adjustment, catalyst stabilization, and integration into continuous-flow systems-are discussed in detail. The impact of these strategies on catalytic performance and furfural selectivity is highlighted, along with a techno-economic analysis showing a promising minimum selling price. Finally, this review addresses the opportunities, challenges, and limitations associated with advancing furfural production in biphasic solvent systems.